2022
DOI: 10.1186/s13045-022-01372-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ERRα promotes cytotoxic effects against acute myeloid leukemia through suppressing mitochondrial oxidative phosphorylation

Abstract: Acute myeloid leukemia (AML) is an aggressive blood cancer with poor clinical outcomes. Emerging data suggest that mitochondrial oxidative phosphorylation (mtOXPHOS) plays a significant role in AML tumorigenesis, progression, and resistance to chemotherapies. However, how the mtOXPHOS is regulated in AML cells is not well understood. In this study, we investigated the oncogenic functions of ERRα in AML by combining in silico, in vitro, and in vivo analyses and showed ERRα is a key regulator of mtOXPHOS in AML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The same study further indicated that ERRα plays a crucial role in regulating mtOXPHOS in AML cells. Intervention with XCT-790, an inverse agonist for ERRα, or through gene knockdown led to a decrease in mtOXPHOS activity, enhancing antileukemic responses both in vitro and in vivo [ 65 ]. However, further investigations into ERR are needed to elucidate its role in HM more comprehensively.…”
Section: Nrs In Hmmentioning
confidence: 99%
“…The same study further indicated that ERRα plays a crucial role in regulating mtOXPHOS in AML cells. Intervention with XCT-790, an inverse agonist for ERRα, or through gene knockdown led to a decrease in mtOXPHOS activity, enhancing antileukemic responses both in vitro and in vivo [ 65 ]. However, further investigations into ERR are needed to elucidate its role in HM more comprehensively.…”
Section: Nrs In Hmmentioning
confidence: 99%
“…Thus, it is not surprising that the transcriptional axis PGC-1α/ERRα is upregulated in several cancer cell types and that its inhibition could undermine cell energy production and thus proliferation. Pharmacologic inhibition or genetic ablation of ERRα reduced the proliferation of acute myeloid leukemia cells [106] and glioma cells [107], both in vitro and in vivo. The inhibition of ERRα function, in addition to reducing mitochondrial energy production, also undermines resistance of tumor cells to oxidative stress, by reducing NADPH content as a consequence of impaired glucose/glutamine oxidation [108], and to hypoxia [57].…”
Section: Errα In Tumorsmentioning
confidence: 99%
“…Estrogen-related receptor α (ERRα) is an orphan nuclear receptor associated with mitochondrial energy production [ 237 ]. To investigate the regulator of mtOXPHOS in AML and explore its associated treatments, Seo et al [ 238 ]. performed sc-RNA sequencing on primary AML cells from patients as well as in vitro and ex vivo analyses in studying the role of ERRα in regulating mtOXPHOS in AML.…”
Section: Omics Studies In Other Approved Targeted Therapiesmentioning
confidence: 99%